Transcriptional regulation of innate lymphoid cells and T cells by aryl hydrocarbon receptor - Helm, Eric Y.; Zhou, Liang (Frontiers in Immunology, 2023)
The aryl hydrocarbon receptor (Ahr) is a ligand-dependent transcription factor and facilitates immune cell environmental sensing through its activation by cellular, dietary, and microbial metabolites, as well as environmental toxins. Although expressed in various cell types, Ahr in innate lymphoid cells (ILCs) and their adaptive T cell counterparts regulates essential aspects of their development and function. As opposed to T cells, ILCs exclusively rely on germ-line encoded receptors for activation, but often share expression of core transcription factors and produce shared effector molecules with their T cell counterparts. As such, core modules of transcriptional regulation are both shared and diverge between ILCs and T cells. In this review, we highlight the most recent findings regarding Ahr’s transcriptional regulation of both ILCs and T cells. Furthermore, we focus on insights elucidating the shared and distinct mechanisms by which Ahr regulates both innate and adaptive lymphocytes.